Needmorella, a new trilobite genus of the Synphoriinae (Dalmanitidae) from the Lower–Middle Devonian of West Virginia. (March 2023) - Holloway, David J.; Scott, Brian M.
Abstract: The trilobite Needmorella new genus, with type species N. simoni new genus new species from the late Emsian to mid-Eifelian Needmore Shale of West Virginia, is a distinctive member of the subfamily Synphoriinae. It also occurs in the same formation in Pennsylvania and Virginia. It is not very similar to other Devonian representatives of the subfamily and is considered to have its origins in a morphologically less-derived ancestor because it shares certain similarities with Silurian genera, including the very short anterior cephalic border unmodified by crenulations or spines, S2 that is not largely reduced to a deep pit adaxially, the relatively low inflation of L3, and the well-defined interpleural furrows on the pygidium. Other particularly distinctive characters of the genus include the very long genal spines and the abaxially inflated and expanded posterior pleural bands on the thorax and pygidium that project slightly distally. The conventional concept of the Devonian synphoriine Anchiopsis Delo, 1935 appears to be incompatible with the holotype of the type species, judging from the early illustrations of the specimen, and the genus could be a synonym of Synphoria Clarke, 1894. UUID: http://zoobank.org/4a820e27-54ec-4f7b-a408-675e62b75154